Perbandingan Kadar D-dimer pada Pasien COVID-19 Bergejala Sedang dan Berat - Kevin J. Walandow; Sylvia R. Marunduh; Joice N. A. Engka (eBiomedik, 2022)
Abstract: Coronavirus disease 2019 (COVID-19) is a disease caused by a new coronavirus called Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Clinical symptoms found in COVID-19 patients vary, ranging from mild, moderate, severe, and asymptomatic. It was found that COVID-19 patients with more severe clinical manifestations tended to have higher D-dimer levels compared to patients with milder clinical manifestations. This study aims to identify the concentration and comparison of D-dimer levels in COVID-19 patients with moderate and severe symptoms. This study used an analytic observational design with a retrospective approach. The research sample amounted to 122 samples derived from medical record data of COVID-19 patients at Sentra Medika Hospital North Minahasa using the purposive sampling method. The levels of D-dimer were then analyzed by the Mann-Whitney test. The results of this study showed that D-dimer levels in COVID-19 patients with moderate symptoms ranged from 137-8,916 ng/mL, while in COVID-19 patients with severe symptoms it ranged from 270-30,540 ng/mL. In the Mann-Whitney test, the value of p = 0.000 (p <0.05). The average D-dimer level in COVID-19 patients with moderate symptoms was 1,659 ± 2,170 ng/mL (n=72) while in COVID-19 patients with severe symptoms it was 4,734 ± 5,999 ng/mL (n=50). In conclusion, there is a significant difference between the average D-dimer levels of moderate and severe COVID-19 patients, where the D-dimer level of severe COVID-19 patients is almost three times higher than that of moderately symptomatic COVID-19 patients.Keywords: COVID-19; D-dimer levels; symptoms Latar Belakang: Coronavirus disease 2019 (COVID-19) merupakan penyakit yang disebabkan oleh virus corona baru yang disebut Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Gejala klinis yang ditemukan pada pasien COVID-19 bervariasi, mulai dari ringan, sedang, berat, dan asimptomatik. Ditemukan pasien COVID-19 dengan manifestasi klinis yang lebih berat cenderung memiliki kadar D-dimer yang lebih tinggi dibandingkan dengan pasien dengan manifestasi klinis lebih ringan. Penelitian ini bertujuan untuk mengidentifikasi konsentrasi dan perbandingan kadar D-dimer pada pasien COVID-19 bergejala sedang dan berat. Penelitian ini menggunakan rancangan observasional analitik dengan pendekatan retrospektif. Sampel penelitian berjumlah 122 sampel yang berasal dari data rekam medis pasien COVID-19 di Sentra Medika Hospital Minahasa Utara menggunakan metode purposive sampling. Kadar D-dimer selanjutnya dianalisis dengan uji Mann-Whitney. Hasil penelitian ini, didapatkan kadar D-dimer pada pasien COVID-19 bergejala sedang berkisar antara 137-8.916 ng/mL, sedangkan pada pasien COVID-19 bergejala berat berkisar antara 270-30.540 ng/mL. Pada uji Mann-Whitney didapatkan nilai p = 0,000 (p < 0,05). Rata-rata kadar D-dimer pasien COVID-19 bergejala sedang sebesar 1.659 ± 2.170 ng/mL (n=72) sedangkan pada pasien COVID-19 bergejala berat sebesar 4.734 ± 5.999 ng/mL (n=50). Sebagai simpulan, terdapat perbedaan yang signifikan dari rata-rata kadar D-dimer pasien COVID-19 bergejala sedang dan berat, dimana kadar D-dimer pada pasien COVID-19 bergejala berat hampir tiga kali lipat lebih tinggi dibandingkan dengan pasien COVID-19 bergejala sedang.Kata Kunci: COVID-19; kadar D-dimer; gejala